Travels with Frances Densmore : her life, work, and legacy in Native American studies - Jensen, Joan M.; Patterson, Michelle Wick, 1973- (University of Nebraska Press, 2015)
Over the first half of the twentieth century, scientist and scholar Frances Densmore (1867-1957) visited thirty-five Native American tribes, recorded more than twenty-five hundred songs, amassed hundreds of artifacts and Native-crafted objects, and transcribed information about Native cultures. Her visits to Indigenous groups included meetings with the Ojibwes, Lakotas, Dakotas, Northern Utes, Ho-chunks, Seminoles, and Makahs. A "New Woman" and a self-trained anthropologist, she not only influenced government attitudes toward Indigenous cultures but also helped mold the field of anthropology. Densmore remains an intriguing historical figure. Although researchers use her vast collections at the Smithsonian and Minnesota Historical Society, as well as her many publications, some scholars critique her methods of "salvage anthropology" and concepts of the "vanishing" Native American. Through narrative descriptions of her life paired with critical essays about her work, this book is a guide for understanding how Densmore formed her collections and the lasting importance they have had for researchers in a variety of fields